Multi-scale fracture characterization method for transitional shale reservoir based on post-stack multi-attribute ant-tracking fusion and pre-stack wide-azimuth gathers AVAZ analysis - Hongjie Peng; Jingtao Zhao; Zhen Qiu; Qin Zhang; Wen Liu; Weiliang Kong; Wanli Gao; Tongjie Sheng; Wenyu Li; Yugang Yang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Transitional shale gas represents a significant domain for exploration in the oil and gas sector. The distribution area is extensive, and the resource potential is significant, representing approximately 25% of China's total shale gas resources. Approaches for predicting reservoir fractures using seismic attributes has been well-established. Seismic attributes are frequently constrained by elements including the frequency and resolution of seismic data. The characteristics of transitional shale reservoirs, including complex lithological combinations, frequent changes in lithology, low resolution and variable frequency of seismic data, as well as the presence of strong reflection shielding in coal seams, significantly influence fracture prediction. The use of a single seismic attribute technique presents challenges in delivering a thorough and precise prediction of fractures within transitional reservoirs. This study extracts discontinuity information of large fractures, fine fractures, and fractures obscured by strong reflections from coal seams using variance attributes, amplitude contrast attributes, and the amplitude of diffracted waves, respectively. The discontinuity features obtained from the three methods are monitored through an ant-tracking technique and integrated. Fractures in the work area are methodically described. The near-offset Rüger formula method is utilized to analyze the pre-stack wide-azimuth gathers. Anisotropic gradients and anisotropic directions have been derived. The results of the fracture prediction are analyzed and validated. A novel and reliable methodology, designed specifically for the challenges of transitional shale reservoirs, has been developed for combined pre-stack and post-stack seismic multi-scale fracture prediction. The robust reflection shielding effect of the coal seam has been effectively eliminated. The characterization of fractures in transitional shale reservoirs has been enhanced.